Pengembangan E-Modul Berbantuan Microsoft Mathematics pada Materi Matriks di MAS Ulumul Qur’an Langsa - Anggreni, Fenny; Faisal, Faisal; Indri Wulandari, Indri Wulandari; Fitriani, Fitriani; Srimuliati, Srimuliati; Zaiyar, M (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
Students' difficulties in understanding mathematical concepts require innovative and interactivelearning media. This study aims to develop an E-Module assisted by Microsoft Mathematics on matrixmaterial for grade XI students at MAS Ulumul Qur’an Langsa using the ADDIE development model(Analysis, Design, Development, Implementation, Evaluation). The study involved 30 students,utilizing observation, tests, and questionnaires as research instruments. Media expert validation resultsshowed an initial score of 80.5%, increasing to 97% in the second stage, while material expert validationachieved 81.25% in the first stage and 92.3% in the second stage, indicating that the E-Module is highlyvalid and feasible for use. Teacher and student evaluations demonstrated high practicality andeffectiveness, with average scores of 87.8% from students and 95.1% from teachers. In conclusion, theMicrosoft Mathematics-assisted E-Module on matrix material is valid, practical, and effective to use asa learning medium on matrix material.